Design of a charge regulator for application in an isolated micro grid with photovoltaic generation - Gómez Paez, Luís Miguel; Guacaneme Muñoz, Wilmer Eduardo; Rodriguez Benavides, Andrés Felipe; Santamaría Piedrahita, Francisco; Trujillo Rodríguez, Cesar Leonardo (Scientia et Technica, 2018)
This paper presents the design of a charge regulatoroperating in an isolated micro grid with photovoltaic generation.The converter selected for this application is a SEPIC with aMPPT algorithm for the cases in which the energy demand isgreater than the energy available. The algorithm is able tomodify its point of maximum power, in order to perform therecharging and supply of power to the battery bank of the system(isolated microgrid) and a group of charges set at a level ofdetermined of voltage. Finally, the results of the tests carried outare presented and the conclusions are given.